If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(y + 5) = 1 + -4y Reorder the terms: -5(5 + y) = 1 + -4y (5 * -5 + y * -5) = 1 + -4y (-25 + -5y) = 1 + -4y Solving -25 + -5y = 1 + -4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '4y' to each side of the equation. -25 + -5y + 4y = 1 + -4y + 4y Combine like terms: -5y + 4y = -1y -25 + -1y = 1 + -4y + 4y Combine like terms: -4y + 4y = 0 -25 + -1y = 1 + 0 -25 + -1y = 1 Add '25' to each side of the equation. -25 + 25 + -1y = 1 + 25 Combine like terms: -25 + 25 = 0 0 + -1y = 1 + 25 -1y = 1 + 25 Combine like terms: 1 + 25 = 26 -1y = 26 Divide each side by '-1'. y = -26 Simplifying y = -26
| x+2(x-1)=-8 | | 5x+10=7(x+2) | | 2x+2(x-1)=-8 | | 3(d+34)-14=45 | | x+x+1=x-1 | | x^2-34x=0 | | 16x-4=33 | | -x+29=-43 | | 2xy= | | (x-1)+4=17 | | 7-3(x-2)=(7-x)4-4x | | 7x-2x(5y-1)= | | 2-x^2+x=0 | | 15+17=13+14 | | -5(x-3)-7x=-36 | | 4x+3=21-2x | | x*x-3-6x=0 | | -2(1+8)=x | | 4x-4=80 | | 6(x-4)=-2(x+8) | | 10x*8y=960 | | 10+8a=11a-6 | | (x^2+x-4)=0 | | 8x+4y=40 | | 1/2(18x-8)=6x-7/3 | | 6(3-x)-5(2x-4)=4(3x-1)+14 | | 10m=96 | | 2m+5=20-3m | | 7x-5=61 | | 15x+40=175 | | 7x-3=15+x | | 1200=s^2+6s |